The webbing of public law: Looking through deportation doctrine - Kaushal, Asha (Osgoode Hall law journal (1960), 2022)
The process of deporting non-citizens is subject to judicial review under several fields of public law. These fields-criminal law, constitutional law, and administrative law-arc towards the protection of the individual. And yet, a series of judicial interpretations place deportees on the margins of that otherwise protective arc. This marginalization is principally explained by the relationships between the fields: The "webbing" of public law joins the fields of criminal law, constitutional law, and administrative law together. Reading deportation cases laterally across these fields reveals that they function as mutual referents for one another, providing assurance that some other field will offer legal cover for the deportee, and buttressing the persistent divide between immigration law and other fields of public law. After examining the webbing as an intervening register in public law theory and practice, the article explores the judicial doctrine of deportation in each field and traces the content of the webbing between them.